2011
DOI: 10.1111/j.1528-1167.2011.02978.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital for neonatal seizures in hypoxic ischemic encephalopathy: A pharmacokinetic study during whole body hypothermia

Abstract: SUMMARYPurpose: Therapeutic hypothermia has recently been introduced to treat term newborns with hypoxic-ischemic encephalopathy, of whom more than half have seizures. Phenobarbital is widely used to treat neonatal seizures, but it is unknown whether its pharmacokinetics is affected by hypothermia. We evaluated the influence of hypothermia on phenobarbital pharmacokinetics in asphyxiated newborns. Methods: Nineteen term asphyxiated newborns treated with mild whole body hypothermia, started within 6 h after bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 49 publications
3
50
2
Order By: Relevance
“…Van den Broek et al (2012) postulated that the effect of asphyxia could be predominately driving changes in the PB CL, and the effect of temperature may not have an additional contributing effect. Since the effect of asphyxia on PB PK was not tested by Filippi et al (2011), this could be the main covariate contributing to the discrepancies in conclusions between these two studies. Shellhaas et al (2013) also found no effect of TTM on the clearance of PB in neonates with HIE.…”
Section: Sedatives/anestheticsmentioning
confidence: 89%
See 3 more Smart Citations
“…Van den Broek et al (2012) postulated that the effect of asphyxia could be predominately driving changes in the PB CL, and the effect of temperature may not have an additional contributing effect. Since the effect of asphyxia on PB PK was not tested by Filippi et al (2011), this could be the main covariate contributing to the discrepancies in conclusions between these two studies. Shellhaas et al (2013) also found no effect of TTM on the clearance of PB in neonates with HIE.…”
Section: Sedatives/anestheticsmentioning
confidence: 89%
“…In contrast to Filippi et al (2011), a clinical study performed by van den Broek et al (2012) reported no effect of hypothermia (33.5°C) for 72 hours on PB PK in asphyxiated neonates. This retrospective study identified 31 neonates with HIE who were administered an intravenous loading dose of PB of 20 mg/kg with additional doses administered as needed in subsequent days.…”
Section: Sedatives/anestheticsmentioning
confidence: 90%
See 2 more Smart Citations
“…An additional major practical advantage of DBS sampling is the feasibility of sample collection by patients or their parents/guardians at home, and its shipping to the lab by mail. Therefore, DBS has been regarded as a very popular sample collection technique for pharmacokinetic studies [16,17].…”
Section: Introductionmentioning
confidence: 99%